2018
DOI: 10.4067/s0719-38902018005000405
|View full text |Cite
|
Sign up to set email alerts
|

Carbono Retenido Por La Hojarasca Y Raíces en Diferentes Usos Del Suelo en La Región Del Chaco Semiárido

Abstract: Las prácticas de conservación agrícola y diversos sistemas de producción tradicionales pueden incrementar considerablemente el carbono orgánico en suelos. Con el objetivo de evaluar la acumulación de carbono en biomasa de raíces y hojarasca con diferentes usos del suelo, se realizó un ensayo en el oeste de la provincia del Chaco, Argentina. Los usos de la tierra (tratamientos) evaluados fueron: pastizal natural, pastura implantada, sistema silvopastoril, bosque nativo semiárido y campo agrícola. Se realizaron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
1
Order By: Relevance
“…Likewise, research carried out by Céspedes et al (2012) do not coincide with the present study since they found that in the yellow grass (Sorghastrum setosum Griseb) and the meadow (Cynodon nlemfluencis), quantities of carbon were found between 10.5tC ha -1 and 19.5tC ha -1 . This is possibly due to certain factors that influence the organic carbon content of the soil as stated by Ibrahim et al (2007), which are the history of land use, the biological and physical conditions of the soil, and the history of organic material input that help to determine the rates of change of carbon under the soil when vegetation and management practices have changed, such as deforestation, tillage and land use.…”
contrasting
confidence: 88%
“…Likewise, research carried out by Céspedes et al (2012) do not coincide with the present study since they found that in the yellow grass (Sorghastrum setosum Griseb) and the meadow (Cynodon nlemfluencis), quantities of carbon were found between 10.5tC ha -1 and 19.5tC ha -1 . This is possibly due to certain factors that influence the organic carbon content of the soil as stated by Ibrahim et al (2007), which are the history of land use, the biological and physical conditions of the soil, and the history of organic material input that help to determine the rates of change of carbon under the soil when vegetation and management practices have changed, such as deforestation, tillage and land use.…”
contrasting
confidence: 88%
“…The implementation of direct sowing and the use of crops to maximize the amount of surface residues are frequent practices in order to increase the organic carbon content in the soil [22]. Céspedes et al [23], working in a drier area of the Chaco region, reported that the highest contributions of surface carbon wer by meadows, and by the forest in the first 15 cm of the soil. The rotation of crops allows to improve the soil carbon balance [24]; rotations that include pastures and service crops should be applied immediately in this situation of use.…”
Section: Discussionmentioning
confidence: 99%